2000
DOI: 10.1016/s0006-3495(00)76499-x
|View full text |Cite
|
Sign up to set email alerts
|

Domain Growth, Shapes, and Topology in Cationic Lipid Bilayers on Mica by Fluorescence and Atomic Force Microscopy

Abstract: Domain formation in mica-supported cationic bilayers of dipalmitoyltrimethylammoniumpropane (DPTAP) and dimyristoyltrimethylammoniumpropane (DMTAP), fluorescently doped with an NBD (((7-nitro-2-1, 3-benzoxadiazol-4-yl)amino)caproyl) phospholipid, was investigated with fluorescence microscopy and atomic force microscopy. Heating above the acyl chain melting temperature and cooling to room temperature resulted in nucleation and growth of domains with distinguishable patterns. Fractal patterns were found for DPTA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
60
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(77 citation statements)
references
References 38 publications
17
60
0
Order By: Relevance
“…2D-F) revealed that this probe's association was strongest with the phase that exhibited an average height $1.3 ± 0.3 nm greater than the other phase. This height difference is usually attributed to the difference in lipid acyl chain splay, tilt and/or packing between the neighboring membrane phases (Connell and Smith, 2006;Dufrene and Lee, 2000;Dunn, 1997, 1998;McKiernan et al, 2000;Yang et al, 1994). The taller of these two regions was therefore identified as the more ordered cholesterol-rich L o phase, and confirmed the previously observed phase partitioning behavior of DiI-C 20 .…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…2D-F) revealed that this probe's association was strongest with the phase that exhibited an average height $1.3 ± 0.3 nm greater than the other phase. This height difference is usually attributed to the difference in lipid acyl chain splay, tilt and/or packing between the neighboring membrane phases (Connell and Smith, 2006;Dufrene and Lee, 2000;Dunn, 1997, 1998;McKiernan et al, 2000;Yang et al, 1994). The taller of these two regions was therefore identified as the more ordered cholesterol-rich L o phase, and confirmed the previously observed phase partitioning behavior of DiI-C 20 .…”
Section: Resultssupporting
confidence: 81%
“…SLBs composed of either lipid mixture 1 or 2 were created by the method of vesicle fusion (Brian and McConnell, 1984;McKiernan et al, 2000;Mou et al, 1994). Briefly, 100 lL of the SUV suspension and 2.9 ml of pH 7.4 aqueous buffer were sequentially deposited onto the freshly cleaved mica previously affixed to the glass of the Willco dish.…”
Section: Substrate-supported Lipid Bilayer Formationmentioning
confidence: 99%
“…The Xuid cell was then heated to 70°C for three minutes, and then allowed to cool to room temperature. This heating-cooling step facilitated the nucleation and growth of micron-size gel-phase domains, as has been reported by others (McKiernan et al, 2000). The Xuid cell was then washed sequentially with lipid-and protein-free 10 mM Hepes buVer, pH 7.4, containing 4 mM CaCl 2 , 150 mM NaCl, followed by 10 mM Hepes buVer, pH 7.4, containing 4 mM EDTA, 150 mM NaCl, and 10 mM Hepes buVer, pH 7.4, containing 150 mM NaCl to remove excess solution liposomes prior to confocal-AFM imaging.…”
Section: Coaxial Confocal-afm Imagingsupporting
confidence: 76%
“…Occasionally, the AFM was placed in a 65°C oven for $15 min and then allowed to cool down to room temperature before imaging. This heating and cooling step was necessary for the formation of supported bilayers from the 50 mol% DSPC/50 mol% DOPC lipid mixtures, facilitating the nucleation and growth of micron-size gel-phase domains, as has been reported by others (McKiernan et al, 2000).…”
Section: Supported Planar Lipid Bilayer Formationmentioning
confidence: 60%